Determinants Factors to Increase Dental Care During Pregnancy: A Systematic Review - Pinasti, Restika Anindya; Agustia, Lita (Dentistry Faculty, 2023)
Background: Many pregnant women know less about maintaining healthy teeth and mouth. Pregnancy is a physiological process that causes changes in a woman's body physic and psycho. In order to uphold optimal oral health, it is imperative that dental treatment not be withheld. The dental management of pregnant patients necessitates the incorporation of specific considerations. Objective: This research aims to describe the factors which improve dental and oral health services for antenatal care. Materials and Methods: The analysis method used in this systematic review is descriptive. The strategy used to search for articles using PICO and literature search was conducted in June 2022. The data used in this research were tertiary obtained from previous researchers' study results. The source of tertiary data obtained in the article of the journal International Reputable. The literature search in this systematic review uses the following databases: Scopus, Science Direct, PubMed, and Google Scholar. Searching articles or journals use keywords and boolean operators (AND, OR, and NOT). The evaluation of the systematic review uses the PRISMA checklist to determine whether the studies have been reaching out and are similar to the purpose of a systematic review. The total number of studies was eight articles. Result: Pregnancy should not be considered an absolute reason to defer required dental care. Perceived need, knowledge, awareness, and socioeconomic were identified as factors that could increase visits and dental oral health services for pregnant women. Well-designed studies with reliable outcomes are required to confirm the findings described in this review. Conclusion: promoting dental care during pregnancy requires a multi-faceted approach that involves raising maternal awareness, garnering support from healthcare providers, addressing socioeconomic disparities, and dispelling misconceptions. By integrating oral health into prenatal care and implementing targeted educational programs, healthcare systems can improve dental care utilization among pregnant women, ultimately leading to better maternal and infant oral health outcomes.